2004
DOI: 10.1182/blood-2003-12-4395
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD4+CD8+ T cells are differentiated effector memory cells with antiviral functions

Abstract: IntroductionT-cell development is an ordered process thought to take place exclusively in the thymus where CD4 ϩ CD8 ϩ T cells develop into CD4 ϩ and CD8 ϩ T cells with mutually exclusive expression of these 2 receptors. Mature CD4 ϩ and CD8 ϩ T cells then leave the thymus and enter secondary lymphoid organs where they recognize their cognate antigen in the context of major histocompatibility complex (MHC) class II and class I molecules on antigenpresenting cells. Antigenic stimulation induces proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
219
3
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(268 citation statements)
references
References 40 publications
(42 reference statements)
29
219
3
17
Order By: Relevance
“…Very low percentages of double positive CD41CD81 are normally found in humans (26). We note that the CD4-AmCyan results in a reasonable separation of CD41 T lymphocytes in normal blood, but may present a problem if CD4 is significantly down-regulated in specimens from samples of patients with Acquired Immune Deficiency Syndrome (AIDS).…”
Section: Panel Strategy and Developmentmentioning
confidence: 84%
“…Very low percentages of double positive CD41CD81 are normally found in humans (26). We note that the CD4-AmCyan results in a reasonable separation of CD41 T lymphocytes in normal blood, but may present a problem if CD4 is significantly down-regulated in specimens from samples of patients with Acquired Immune Deficiency Syndrome (AIDS).…”
Section: Panel Strategy and Developmentmentioning
confidence: 84%
“…[42][43][44] Of interest, it has been shown that DP T cells play an important regulatory role in inflammatory bowel disease 33 and may contribute to the adaptative immune response during viral infections. 45 However, little is known regarding their function in cancer, except for one study describing the capacity of DP T cells infiltrating a cutaneous T-cell lymphoma to exert a tumor-specific HLA Class I restricted lysis. 46 In agreement with what was observed for intestinal DP T cells, breast tumor associated DP T cells have an overall higher capacity to produce cytokines than SP T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, numerous studies reported the presence of DP T cells with, in most cases, an increased frequency in the blood and/or in the target organ of several pathological conditions (for review see [9]), such as autoimmune diseases [10][11][12], inflammation disorders [13,14], allergies [15,16], infectious diseases [17][18][19], and cancer, postulating their involvement in pathologic events [20][21][22][23]. In these contexts, diverse functions of DP T cells were observed from cytotoxic activity [22,24] to regulatory properties [25], as well as helper potential [10].…”
Section: Introductionmentioning
confidence: 99%